Pistol shipping receipt
Shipping receipt dated 1946-05-06, for sending one of Steinbeck's pistol from Monterey to 175 East 78th Street, his home in New York City. The receipt is signed by George Doroles, a member of the Monterey Police Department. For more detail, see photo 1 885. High-quality color photocopy only.